Water Sensitive Cities Index: A diagnostic tool to assess water sensitivity and guide management actions - Rogers, B.C.; Dunn, G.; Hammer, K.; Novalia, W.; de Haan, F.J.; Brown, L.; Brown, R.R.; Lloyd, S.; Urich, C.; Wong, T.H.F.; Chesterfield, C. (Water research (Oxford), 2020)
•Presents the Water Sensitive Cities Index, a new benchmarking and diagnostic tool.•Used to define, assess and operationalize a city's water sensitive performance.•Novel assessment methodology is based on a collaborative stakeholder process.•Application is demonstrated for three diverse Australian cities.•Helps develop collective commitment and evidence-based priorities for action. Cities are wrestling with the practical challenges of transitioning urban water services to become water sensitive; capable of enhancing liveability, sustainability, resilience and productivity in the face of climate change, rapid urbanisation, degraded ecosystems and ageing infrastructure. Indicators can be valuable for guiding actions for improvement, but there is not yet an established index that measures the full suite of attributes that constitute water sensitive performance. This paper therefore presents the Water Sensitive Cities (WSC) Index, a new benchmarking and diagnostic tool to assess the water sensitivity of a municipal or metropolitan city, set aspirational targets and inform management responses to improve water sensitive practices. Its 34 indicators are organised into seven goals: ensure good water sensitive governance, increase community capital, achieve equity of essential services, improve productivity and resource efficiency, improve ecological health, ensure quality urban spaces, and promote adaptive infrastructure. The WSC Index design is a quantitative framework based on qualitative rating descriptions and a participatory assessment methodology, enabling local contextual interpretations of the indicators while maintaining a robust universal framework for city comparison and benchmarking. The paper demonstrates its application on three illustrative cases. Rapid uptake of the WSC Index in Australia highlights its value in helping stakeholders develop collective commitment and evidence-based priorities for action to accelerate their city's water sensitive transition. Early testing in cities in Asia, the Pacific and South Africa has also showed the potential of the WSC Index internationally. [Display omitted]